Metabolic characteristics and genomic epidemiology of Escherichia coli serogroup O145 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University, Palmerston North, New Zealand - Collis, Rose (Massey University, 2018)
Shiga toxin-producing Escherichia coli (STEC) are a global public health concern, and can cause severe human disease. Ruminants are asymptomatic reservoirs of STEC, shedding this pathogen via their faeces. There is ‘zero tolerance’ for the Top 7 STEC serogroups (O26, O45, O103, O111, O121, O145 and O157) in ground beef products exported to the USA. STEC may contaminate carcasses during processing and therefore are a major regulatory concern for New Zealand’s meat industry. A previous study investigating the prevalence of STEC in young calves (n=1508) throughout New Zealand identified STEC O145 as the most prevalent serogroup (43%) at the dairy farm level compared to the other Top 7 serogroups. This high prevalence underlines STEC O145 as a public health concern and an issue for the meat industry. Current culture-based methods for STEC detection are not fully discriminatory due to the lack of consistent differential characteristics between STEC and non-pathogenic E. coli. This study aims to (i) investigate metabolic characteristics of E. coli O145 to facilitate the differential culture of this serogroup and (ii) understand the genomic epidemiology of E. coli O145 using whole genome sequencing (WGS). E. coli O145 strains examined in this study were genetically and metabolically diverse, according to carbon utilisation. The metabolic and genomic analyses were unable to differentiate between stx-positive and stx-negative O145 strains and there was no association with isolation source. However, clustering of O145 strains was observed according to multi-locus sequence type and at the level of eae subtype, a gene encoding the protein intimin which is involved in bacterial attachment to intestinal epithelial cells. Carbon substrates such as D-serine and D-malic acid were identified as candidate metabolites to differentiate defined O145 sequence types and may assist with identification in conjunction with currently available molecular methods. This research has demonstrated the genetic heterogeneity of serogroup O145 and has made significant progress in the identification of metabolites that may prove beneficial in the development of a differential media for certain subsets of serogroup O145. Such a medium would prove a valuable tool for maintaining and monitoring public health and providing food quality and safety assurances that New Zealand meat for export is free of this pathogen.
Keywords: Escherichia coli; Escherichia coli infections in animals|xEpidemiology; Meat|xMicrobiology